Measuring racial bias in employment services in Colombia - Suzanne Duryea; Jaime Millán-Quijano; Judith Morrison; Yanira Marcela Oviedo Gil (Inter-American Development Bank (IDB), 2024)
In this paper, we document de facto, implicit, and explicit racial biases within the public employment service in Colombia. By combining administrative data about job seekers and job openings with direct surveys to job counselors, including a Race Implicit Association Test, we compute different types of racial bias. We find that while job counselors do not self-report biased attitudes against Afro-descendant individuals, the majority exhibit high levels of implicit bias, which also correlates strongly with observed lower referral rates of Afro-descendants to job openings. In addition, we randomly provide information to job counselors about their implicit bias and test if this information changes their referral behavior. While we demonstrate that the implicit bias of counselors is a major contributor to racial gaps in labor outcomes, we do not find that providing feedback on this unconscious bias changes their referral behavior.
Keywords: J15; J21; J71; 330; Implicit stereotypes; labor market discrimination; developing countries